Features of personnel management - Kramskoi, O. Ju.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It has been proved that effective personnel management helps to increase the competitiveness of an enterprise in the modern market; affects the efficiency of labor and production processes (achieving maximum profit); ensures high social efficiency of the team.
Особливості управління персоналом
Keywords: personnel; management; enterprises; competitiveness; principles; psychology